A Global Bibliometric Analysis of Loneliness During the COVID-19 Pandemic: Future research and policy implications - Trinh Thi Xuan Nguyen; Sumeet Lal; Yoshihiko Kadoya (Asia Pacific Journal of Health Management)
Introduction: Under the profound impacts of the COVID-19 pandemic, loneliness has become a major public health concern worldwide. This study is conducted to systematically evaluate existing literature on loneliness during the pandemic to identify research trends and knowledge gaps for future studies and policy developments.